(untitled) (Communications in Computational Physics, 2018)
Coarse-grained molecular dynamics simulations of DPPC lipid bilayers were performed with different system sizes at T = 323 K for a period of 1 µs. The structural properties of the systems were demonstrated by examining the area and volume per lipid, electron density profile, order parameter, and the lipid bilayer thickness. It was shown that the finite system size has a negligible effect on the ensemble averages of the area and volume per lipid, the order parameter, and the bilayer thickness. However, the electron density profiles become smoother and wider at a larger system size due to the increasing surface/interface fluctuation from undulations. On the other hand, the lipid dynamics was quantified by computing the lateral diffusion coefficients of DPPC molecules. It was revealed that, the effective lateral diffusion coefficient of DPPC increases initially by 19% as the bilayer increases from 64 to 256 lipids per leaflet, and then it changes slightly and fluctuates around a steady value as the system further expands.